Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the equation [tex]\(2 \log_2 x - \log_2(2x) = 3\)[/tex], let's break it down step by step.
1. Express the logarithm: The equation [tex]\(2 \log_2 x - \log_2(2x) = 3\)[/tex] involves logarithms, so let's simplify the expression on the left-hand side using properties of logarithms.
2. Logarithm properties: Recall the logarithm properties:
- [tex]\(\log_b(mn) = \log_b m + \log_b n\)[/tex]
- [tex]\(\log_b(m/n) = \log_b m - \log_b n\)[/tex]
We need to simplify [tex]\(\log_2(2x)\)[/tex]. Using the property that [tex]\(\log_b(mn) = \log_b m + \log_b n\)[/tex], we can write:
[tex]\[ \log_2(2x) = \log_2 2 + \log_2 x \][/tex]
Since [tex]\(\log_2 2 = 1\)[/tex], we can substitute:
[tex]\[ \log_2(2x) = 1 + \log_2 x \][/tex]
3. Substitute and simplify: Substitute [tex]\(\log_2(2x)\)[/tex] in the original equation.
[tex]\[ 2 \log_2 x - (1 + \log_2 x) = 3 \][/tex]
Simplify the left-hand side:
[tex]\[ 2 \log_2 x - 1 - \log_2 x = 3 \][/tex]
Combine the logarithms:
[tex]\[ \log_2 x - 1 = 3 \][/tex]
4. Isolate the logarithm:
[tex]\[ \log_2 x = 4 \][/tex]
5. Solve for [tex]\(x\)[/tex]: Recall the definition of a logarithm. If [tex]\(\log_2 x = 4\)[/tex], then:
[tex]\[ x = 2^4 \][/tex]
Calculate the power:
[tex]\[ x = 16 \][/tex]
So, the correct answer is [tex]\(C. x = 16\)[/tex].
1. Express the logarithm: The equation [tex]\(2 \log_2 x - \log_2(2x) = 3\)[/tex] involves logarithms, so let's simplify the expression on the left-hand side using properties of logarithms.
2. Logarithm properties: Recall the logarithm properties:
- [tex]\(\log_b(mn) = \log_b m + \log_b n\)[/tex]
- [tex]\(\log_b(m/n) = \log_b m - \log_b n\)[/tex]
We need to simplify [tex]\(\log_2(2x)\)[/tex]. Using the property that [tex]\(\log_b(mn) = \log_b m + \log_b n\)[/tex], we can write:
[tex]\[ \log_2(2x) = \log_2 2 + \log_2 x \][/tex]
Since [tex]\(\log_2 2 = 1\)[/tex], we can substitute:
[tex]\[ \log_2(2x) = 1 + \log_2 x \][/tex]
3. Substitute and simplify: Substitute [tex]\(\log_2(2x)\)[/tex] in the original equation.
[tex]\[ 2 \log_2 x - (1 + \log_2 x) = 3 \][/tex]
Simplify the left-hand side:
[tex]\[ 2 \log_2 x - 1 - \log_2 x = 3 \][/tex]
Combine the logarithms:
[tex]\[ \log_2 x - 1 = 3 \][/tex]
4. Isolate the logarithm:
[tex]\[ \log_2 x = 4 \][/tex]
5. Solve for [tex]\(x\)[/tex]: Recall the definition of a logarithm. If [tex]\(\log_2 x = 4\)[/tex], then:
[tex]\[ x = 2^4 \][/tex]
Calculate the power:
[tex]\[ x = 16 \][/tex]
So, the correct answer is [tex]\(C. x = 16\)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.